Weak GPS Signal Acquisition Algorithm Based on Chaotic Oscillator. (30th September 2009) - Huang, Pengda; Pi, Yiming; Zhao, Zhiqin
Abstract : To detect weak Global Position System (GPS) signal indoors, various high-sensitivity detection algorithms have been proposed. However, a common tradeoff between high-sensitivity and computation burden impedes development of high sensitivity GPS receiver. As another strategy, chaotic oscillator, sensitive to periodic signal and inert to noise, possesses huge advantage in weak signal acquisition. In this paper chaotic oscillator is employed in weak GPS signal acquisition. With numerical indication of Lyapunov exponents (LEs), chaotic oscillator can achieve acquisition in extremely weak GPS signal. Compared with conventional algorithm, chaotic oscillator consumes less acquisition time and is capable of detecting weak GPS signal. In the final section of paper, results from computer simulation illustrate that chaotic oscillator algorithm can acquire GPS signal at− 48 dB/2MHz SNR.